HIV Transmission to Premature Very Low Birth Weight Infants. Issue 9 (September 2017) - Levin, Candyce; Le Roux, David M.; Harrison, Michael C.; Tooke, Lloyd
Abstract : Abstract: There is sparse literature about HIV transmission in preterm infants. Eighty-two HIV-exposed preterm infants received birth polymerase chain reactions (PCRs). Five (6.1%) were HIV positive with all 5 mothers receiving inadequate antiretrovirals. Of the PCR-negative infants, 9 died and 87% of the survivors received further PCR testing which remained negative. With correct care, intrapartum transmission of HIV can virtually be eliminated.